Salivary steroids at rest and after a training load in young male athletes: Relationship with chronological age and pubertal development - Di Luigi, L.; Baldari, C.; Gallotta, M. C.; Perroni, F.; Romanelli, F.; Lenzi, A.; Guidetti, L. (International Journal of Sports Medicine, 2006)
Puberty influences both the performance and the hormonal responses to exercise-related stress. We evaluated the distribution and the correlation between pubertal characteristics and the salivary cortisol (sC) and testosterone (sT) responses to acute physical exercise in young male athletes (13.4 ± 2.1 yr, n = 110). The mean pre-exercise nmol · L-1 sC and sT concentrations were 19.08 ± 4.32 and 0.34 ± 0.15 and increased to 21.27 ± 5.51 and 0.41 ± 0.16 after a 90-min training session (p < 0.01). The sC concentration at rest was positively correlated with chronological age (p < 0.01) and negatively correlated with fat % (p < 0.05), whereas significant negative correlations of ?sC and ?sC% after exercise with age, pubertal stage and mean testis volume (p < 0.05) were observed. The sT increase after exercise was correlated with chronological age, pubertal stage and pre-exercise sT levels (p < 0.01), whereas the ?sT and ?sT% of increase were negatively correlated with chronological age and resting sT levels (p < 0.05 and p < 0.01). In the present study, we observed the presence of high inter-individual variability of different biological parameters (anthropometry, pubertal stage, hormones, etc.) within athletes selected by chronological age in the same class and the presence of significant correlations between chronological age, puberty and the steroid hormone responses to physical exercise. Our data suggest the need for different criteria in exercise prescription and selection of young athletes and in the evaluation of stress reactivity at puberty.